Insights into Khaldun's Legacy: Ideal Methods in Arabic Language Instruction - Fradana, Heru (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
Ibn Khaldun was a multidimensional Muslim scholar in the 14th century, born in Tunisia, who excelled as a historian, philosopher, sociologist, and economist. His significant work, the